Synthesis and Characterization of Multifunctional Branched Amphiphilic Peptide Bilayer Conjugated Gold Nanoparticles - Natarajan, Pavithra; Sukthankar, Pinakin; Changstrom, Jessica; Holland, Christopher S.; Barry, Shannon; Hunter, Wayne B.; Sorensen, Christopher M.; Tomich, John M. (My University, 2018)
We provide strong chemical and biophysical evidence that documents that branched amphiphilic peptides, BAPs, known to assemble into spherical nanoassemblies in solution, do assemble as peptide-bilayer-delimited capsules. These nanoassemblies are termed branched amphiphilic peptide capsules (BAPCs). BAPCs are taken up by cells and accumulate in the perinuclear region to persist there without apparent degradation. BAPCs also entrap small proteins and solutes and stably encapsulate α-particle-emitting radionuclides. We have devised a method utilizing thiol chemistry to conjugate these peptide sequences onto gold nanoparticles (≤5 nm) with the objective of demonstrating the assembly of these peptides into a bilayer. The peptides are initially assembled as a monolayer on the gold surface via interaction with cysteine residues on the peptide C-terminus in an organic solvent. The subsequent transition of these peptide-monolayer-protected gold nanoparticles to an aqueous solution in the presence of excess peptides led to the formation of the peptide bilayer on the gold surface. The approach was exploited further to produce bilayer-coated magnetic nanoparticles. The innovation described in this study provides a stable metallic nanoparticle–peptide conjugate system that will help to determine interactions of BAPs in a biological system, with relative ease, important for developing future applications such as simultaneous delivery and imaging of surface-bound molecules of interest.
Citation: Natarajan, P., Sukthankar, P., Changstrom, J., Holland, C. S., Barry, S., Hunter, W. B., … Tomich, J. M. (2018). Synthesis and Characterization of Multifunctional Branched Amphiphilic Peptide Bilayer Conjugated Gold Nanoparticles. ACS Omega, 3(9), 11071–11083. https://doi.org/10.1021/acsomega.8b01633
Keywords: Drug delivery systems; Peptides and Proteins; Thin films